Disease Perception and Duration of Suffering with Self-Care Management in Patients with Diabetes Mellitus - Wibowo, Wibowo; Suprapto, Suprapto; Kamaruddin, Muh Ihsan; Nurlina, Nurlina; Mangaya Takke, Jessy Andre (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Diabetes Mellitus (DM) is a chronic metabolic disorder requiring continuous medical care and patient self-management to prevent complications. Perception of disease and the duration of suffering may influence how patients manage their condition through self-care behaviors. Understanding this relationship is crucial for developing targeted interventions to improve patient outcomes. This study examines the relationship between disease perception and duration of illness with self-care management in patients with diabetes mellitus. Research Methodology: This quantitative analytical study employed a cross-sectional design involving 150 patients diagnosed with diabetes mellitus at a public health center. Data were collected using validated questionnaires assessing disease perception and self-care management, along with patient medical records to determine the duration of the disease. Statistical analysis was performed using Pearson correlation and multiple regression tests to examine the relationship between disease perception, duration of suffering, and self-care management. Result: The study found a significant positive correlation between disease perception and self-care management (r = 0.62, p < 0.01). Additionally, patients with a longer duration of suffering demonstrated better self-care practices (r = 0.45, p < 0.05). Multiple regression analysis revealed that disease perception was a stronger predictor of self-care management than duration of illness (β = 0.58, p < 0.01). Conclusion: A higher perception of the seriousness and controllability of diabetes mellitus positively influences patients' self-care management. Duration of illness also contributes, though to a lesser extent. Health practitioners should enhance patients’ understanding and perception of their disease to improve self-care outcomes.